Upaya Integrasi Penanganan Nyeri Haid dengan Abdominal Stretching pada Remaja Puteri di Pesantren Baitul Ulum El-Musawwa, Serang, Banten - Desmawati Desmawati (Jurnal Abdimas Kesehatan (JAK), 2021)
Menstrual pain or dysmenorrhea is a problem that is often faced by teenagers during menstruation. Dysmenorrhea occurs due to an imbalance of the hormone progesterone which causes uterine contractions and stimulate the pain response of each individual. Based on the underlying pathophysiology, there are two types of dysmenorrhea, namely primary dysmenorrhea and secondary dysmenorrhea, primary dysmenorrhea occurs in women of childbearing age in the form of pain in the lower abdomen so that it can disrupt their quality of life. Dysmenorrhea often interferes with teenagers' productivity and influences coping abilities. The purpose was to evaluate the abdominal stretching on the intensity of menstrual pain (dysmenorrhea) in teenagers. This public service is a test pre-test of pain menstrual by using Visual Analogue Scale, demonstration-re-demonstration abdominal stretching, and evaluate pain scale of dysmenorrhea. From 26 participants founding that the level of menstrual pain at middle is 69.23%, lower is 30.77%, there are no severe pain levels. After abdominal stretching reduce the pain become 100% at lower pain and there are no moderate and severe pain levels. The Abdominal stretching exercise is recommended to be another alternative for reducing dysmenorrhea in teenagers that is easy, economic, safe and without side effects